Fiction and truth about the decade of development - Broekmeijer, M. W. J. M. (Leyden : A. W. Sijthoff, 1966)
This book is about tremendous problem in our present world resulting from the unevenness of economic and social development
include index
Bibliography: p. [147]-149.
asm; 04/03/19
Loans
Keywords: Economic development; Developing countries